The “Boat Place” Burial: New Skeletal Evidence from the 1845 Franklin Expedition - Stenton, Douglas R.; Keenleyside, Anne; Park, Robert W. (ARCTIC, 2015)
In 2013, a burial feature was excavated at NgLj-3, a Franklin expedition archaeological site on the Erebus Bay coast of King William Island. The feature contained 72 human bones representing a minimum of three individuals. The composition of the assemblage closely matches the description of skeletal remains of members of the Franklin expedition buried by Frederick Schwatka in 1879. Analysis suggests that the remains include those of the two men discovered in a ship’s boat in 1859 by the McClintock search expedition. En 2013, un aménagement de sépulture a été dégagé à NgLj-3, site archéologique de l’expédition Franklin sur la côte de la baie Erebus, à l’île King William. Cet aménagement comprenait 72 os humains appartenant à au moins trois personnes. La composition de cet assemblage s’apparente étroitement à la description des restes humains des membres de l’expédition Franklin inhumés par Frederick Schwatka en 1879. Selon des analyses, les restes comprennent ceux de deux hommes découverts dans le bateau d’un navire par l’expédition de recherche McClintock en 1859.